Computer aided design of membrane processes for effluent treatment and Cr(VI) recovery for reuse on-site - Corvalan, Sergio (2003)
The design of a nondispersive solvent extraction plant for effluent treatment and Cr(VI) recovery for recycle and reuse on-site is presented. The process has an extraction sector where Cr(VI) is extracted from the effluent and transferred to an organic solution and the stripping sector where Cr(VI) is back-extracted from the organic solution into an aqueous phase and concentrated for recycle and reuse on-site. The amount of Cr(VI) disposed of into the environment is reduced, leading to a clean technology. The design is formulated as a nonlinear programming problem including the differential equations that model the mass transfer in the membrane modules as equality constraints. The optimization variables are the membrane areas required in the extraction and stripping sectors as design variables and the organic and stripping flowrates as operating variables. The membrane areas required in the extraction and stripping sectors for the countercurrent and co-current operations are compared at different effluent Cr(VI) compositions. The countercurrent operation requires a significantly smaller area than the co-current operation in the stripping sector at high effluent Cr(VI) content. The ratios of Cr(VI) recovered moles by membrane area as a function of Cr(VI) recoveries are reported, indicating different cost levels of this process.